2001
DOI: 10.1152/jn.2001.86.4.1685
|View full text |Cite
|
Sign up to set email alerts
|

Grasp With Hand and Mouth: A Kinematic Study on Healthy Subjects

Abstract: Neurons involved in grasp preparation with hand and mouth were previously recorded in the premotor cortex of monkey. The aim of the present kinematic study was to determine whether a unique planning underlies the act of grasping with hand and mouth in humans as well. In a set of four experiments, healthy subjects reached and grasped with the hand an object of different size while opening the mouth (experiments 1 and 3), or extending the other forearm (experiment 4), or the fingers of the other hand (experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 31 publications
10
129
2
2
Order By: Relevance
“…Concurrent contraction of other facial muscles not directly involved in articulation was not observed during these acts (Higginbotham et al , 2008). This observation mimics the hand-mouth activity in non-human primates and prelinguistic infants, and the influence of grasping on labial articulation in adult humans (Gentilucci et al , 2001). It also supports the idea that there is a transition from gestural to verbal, articulate communication systems.…”
Section: Mirror Neurons In Language and Gesturesupporting
confidence: 76%
“…Concurrent contraction of other facial muscles not directly involved in articulation was not observed during these acts (Higginbotham et al , 2008). This observation mimics the hand-mouth activity in non-human primates and prelinguistic infants, and the influence of grasping on labial articulation in adult humans (Gentilucci et al , 2001). It also supports the idea that there is a transition from gestural to verbal, articulate communication systems.…”
Section: Mirror Neurons In Language and Gesturesupporting
confidence: 76%
“…The motor coupling is believed to occur due to shared neural resources for hand actions (Iacoboni et al, 1998) and actual or internal speech (Hinke et al, 2003) and is further supported by behavioral evidence demonstrating selective disruption of speech syllables when the hands are required to perform non-congruent articulations (Gentilucci et al, 2001). However, tongue protrusions were also reported during the Story Recall task that had no manual motor requirement.…”
Section: Rates Of Tongue Protrusionsmentioning
confidence: 87%
“…For example, chimpanzees generated sympathetic mouth movements significantly more often during tasks requiring fine motor manipulation compared with tasks requiring gross motor actions (Waters & Fouts, 2002). In humans, Gentilucci, Benuzzi, Gangitano, and Grimaldi (2001) demonstrated that the pronunciation of a syllable could be selectively disrupted when producing a simultaneous grasping action for target objects of a non-congruent size to that of the mouth vocalization. The finding suggests that the fine motor articulation required for grasping is processed similarly by both hand and mouth in humans, thus they tend to complement each other.…”
Section: Introductionmentioning
confidence: 99%
“…Several works by Gentilucci and colleagues (Gentilucci, 2003;Gentilucci, Benuzzi, Gangitano, & Grimaldi, 2001, Gentilucci, Santunione, Roy, & Stefanini, 2004aGentilucci, Stefanini, Roy, & Santunione, 2004b) have shown a close relationship between speech production and the execution/observation of arm and hand gestures. In one of these studies, Gentilucci et al (2004a) showed that the execution/observation of the action of bringing an object to the mouth activates a mouth articulation posture likely related to food manipulation, which selectively influences speech production.…”
Section: Embodied Simulation At the Vehicle Levelmentioning
confidence: 97%